Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine whether the given points lie on the graph of the linear function [tex]\( y = 2x + 3 \)[/tex], we will substitute the [tex]\( x \)[/tex]-coordinate of each point into the equation and check if the resulting [tex]\( y \)[/tex]-value matches the [tex]\( y \)[/tex]-coordinate of the point.
Let's analyze each point one by one:
### Point [tex]\((-1, 1)\)[/tex]
1. Substitute [tex]\( x = -1 \)[/tex] into the equation [tex]\( y = 2x + 3 \)[/tex]:
[tex]\[ y = 2(-1) + 3 = -2 + 3 = 1 \][/tex]
2. The [tex]\( y \)[/tex]-value we calculated is [tex]\( 1 \)[/tex], which matches the [tex]\( y \)[/tex]-coordinate of the point [tex]\((-1, 1)\)[/tex].
Thus, the point [tex]\((-1, 1)\)[/tex] lies on the graph.
### Point [tex]\((-4, -6)\)[/tex]
1. Substitute [tex]\( x = -4 \)[/tex] into the equation [tex]\( y = 2x + 3 \)[/tex]:
[tex]\[ y = 2(-4) + 3 = -8 + 3 = -5 \][/tex]
2. The [tex]\( y \)[/tex]-value we calculated is [tex]\( -5 \)[/tex], which does not match the [tex]\( y \)[/tex]-coordinate of the point [tex]\((-4, -6)\)[/tex].
Thus, the point [tex]\((-4, -6)\)[/tex] does not lie on the graph.
### Point [tex]\((0, -2)\)[/tex]
1. Substitute [tex]\( x = 0 \)[/tex] into the equation [tex]\( y = 2x + 3 \)[/tex]:
[tex]\[ y = 2(0) + 3 = 0 + 3 = 3 \][/tex]
2. The [tex]\( y \)[/tex]-value we calculated is [tex]\( 3 \)[/tex], which does not match the [tex]\( y \)[/tex]-coordinate of the point [tex]\((0, -2)\)[/tex].
Thus, the point [tex]\((0, -2)\)[/tex] does not lie on the graph.
### Point [tex]\((-2, -1)\)[/tex]
1. Substitute [tex]\( x = -2 \)[/tex] into the equation [tex]\( y = 2x + 3 \)[/tex]:
[tex]\[ y = 2(-2) + 3 = -4 + 3 = -1 \][/tex]
2. The [tex]\( y \)[/tex]-value we calculated is [tex]\( -1 \)[/tex], which matches the [tex]\( y \)[/tex]-coordinate of the point [tex]\((-2, -1)\)[/tex].
Thus, the point [tex]\((-2, -1)\)[/tex] lies on the graph.
### Conclusion
After checking each point, we find that the points [tex]\((-1, 1)\)[/tex] and [tex]\((-2, -1)\)[/tex] lie on the graph of the function [tex]\( y = 2x + 3 \)[/tex].
Let's analyze each point one by one:
### Point [tex]\((-1, 1)\)[/tex]
1. Substitute [tex]\( x = -1 \)[/tex] into the equation [tex]\( y = 2x + 3 \)[/tex]:
[tex]\[ y = 2(-1) + 3 = -2 + 3 = 1 \][/tex]
2. The [tex]\( y \)[/tex]-value we calculated is [tex]\( 1 \)[/tex], which matches the [tex]\( y \)[/tex]-coordinate of the point [tex]\((-1, 1)\)[/tex].
Thus, the point [tex]\((-1, 1)\)[/tex] lies on the graph.
### Point [tex]\((-4, -6)\)[/tex]
1. Substitute [tex]\( x = -4 \)[/tex] into the equation [tex]\( y = 2x + 3 \)[/tex]:
[tex]\[ y = 2(-4) + 3 = -8 + 3 = -5 \][/tex]
2. The [tex]\( y \)[/tex]-value we calculated is [tex]\( -5 \)[/tex], which does not match the [tex]\( y \)[/tex]-coordinate of the point [tex]\((-4, -6)\)[/tex].
Thus, the point [tex]\((-4, -6)\)[/tex] does not lie on the graph.
### Point [tex]\((0, -2)\)[/tex]
1. Substitute [tex]\( x = 0 \)[/tex] into the equation [tex]\( y = 2x + 3 \)[/tex]:
[tex]\[ y = 2(0) + 3 = 0 + 3 = 3 \][/tex]
2. The [tex]\( y \)[/tex]-value we calculated is [tex]\( 3 \)[/tex], which does not match the [tex]\( y \)[/tex]-coordinate of the point [tex]\((0, -2)\)[/tex].
Thus, the point [tex]\((0, -2)\)[/tex] does not lie on the graph.
### Point [tex]\((-2, -1)\)[/tex]
1. Substitute [tex]\( x = -2 \)[/tex] into the equation [tex]\( y = 2x + 3 \)[/tex]:
[tex]\[ y = 2(-2) + 3 = -4 + 3 = -1 \][/tex]
2. The [tex]\( y \)[/tex]-value we calculated is [tex]\( -1 \)[/tex], which matches the [tex]\( y \)[/tex]-coordinate of the point [tex]\((-2, -1)\)[/tex].
Thus, the point [tex]\((-2, -1)\)[/tex] lies on the graph.
### Conclusion
After checking each point, we find that the points [tex]\((-1, 1)\)[/tex] and [tex]\((-2, -1)\)[/tex] lie on the graph of the function [tex]\( y = 2x + 3 \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.